Advancing targeted protein degradation for metabolic diseases therapy. (February 2023) - Zhou, Qian-Qian; Xiao, Hai-Tao; Yang, Fan; Wang, Yong-Dan; Li, Ping; Zheng, Zu-Guo
Abstract: The development and application of traditional drugs represented by small molecule chemical drugs and biological agents, especially inhibitors, have become the mainstream drug development. In recent years, targeted protein degradation (TPD) technology has become one of the most promising methods to remove specific disease-related proteins using cell self-destruction mechanisms. Many different TPD strategies are emerging based on the ubiquitin-proteasome system (UPS) and the autophagy-lysosomal pathway (ALP), including but not limited to proteolysis-targeting chimeras (PROTAC), molecular glues (MG), lysosome targeting chimeras (LYTAC), chaperone-mediated autophagy (CMA)-targeting chimeras, autophagy-targeting chimera (AUTAC), autophagosome-tethering compound (ATTEC), and autophagy-targeting chimera (AUTOTAC). The advent of targeted degradation technology can change most protein targets in human cells from undruggable to druggable, greatly expanding the therapeutic prospect of refractory diseases such as metabolic syndrome. Here, we summarize the latest progress of major TPD technologies, especially in metabolic syndrome and look forward to providing new insights for drug discovery. Graphical Abstract: ga1